2018
DOI: 10.3892/etm.2018.6770
|View full text |Cite
|
Sign up to set email alerts
|

TNF‑α increases the expression of inflammatory factors in synovial fibroblasts by inhibiting the PI3K/AKT pathway in a rat model of monosodium iodoacetate‑induced osteoarthritis

Abstract: Osteoarthritis is a degenerative disease that often causes patients to experience joint pain and deformity. It has been demonstrated that tumor necrosis factor (TNF)-α is associated with the progression of osteoarthritis; however, to the best of our knowledge, the mechanisms by which TNF-α simulates the progression of osteoarthritis and the signaling pathway(s) it influences remain unknown. Therefore, the aim of the present study was to investigate the therapeutic effects of TNF-α inhibitor in an iodoacetate-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…They can degrade ECM of the articular cartilage, which mainly consists of collagens and proteoglycans. MMP-3, MMP-9, and MMP-13 levels increased in animals induced with osteoarthritis [18,30,33,34,63], but the TIMP-2 level was shown to decline [72]. Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 97%
See 2 more Smart Citations
“…They can degrade ECM of the articular cartilage, which mainly consists of collagens and proteoglycans. MMP-3, MMP-9, and MMP-13 levels increased in animals induced with osteoarthritis [18,30,33,34,63], but the TIMP-2 level was shown to decline [72]. Similarly, MMP-13, MMP-3, MMP-2, and MMP-9 increased in the cell line model of osteoarthritis [26,28].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 97%
“…Upon stimulation, the cells release IL-6 [26], IL-8 [27], IL-10 [28], IL-1β [29], and TNF-α [28]. Similar cytokine profile was increased in animal models of osteoarthritis [18,[30][31][32][33][34].…”
Section: The Role Of Cytokines In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor necrosis factor (TNF) α has been shown to be associated with the progression of osteoarthritis. It has been shown that TNF-α is capable of regulating in ammation in an osteoarthritis rat model by downregulating the signaling pathway of phosphoinositide 3-kinase / protein kinase B (PI3K / AKT) in synovial broblasts [4].…”
Section: Introductionmentioning
confidence: 99%
“…So, our data were partly in accordance with previous data. In addition, we also identi ed new signaling pathways including TNF signaling pathway, NOD-like receptor signaling pathway and HIF-1 signaling pathway, which were all the core signaling pathway in the pathogenesis of OA [31][32][33][34][35][36], thus may be involved in the inhibitive effect of Scutellarin on OA. Our data will be the supplement for the present studies on the molecular mechanisms of Scutellarin against OA.…”
Section: Discussionmentioning
confidence: 99%